Pengaruh Waktu Yang Berbeda Terhadap Suhu, pH, dan Oksigen Terlarut Pada Indoor Hatchery - Syauqi Adithiya; Suri Purnama Febri; Siti Komariyah; Teuku Fadlon Haser; Rinaldi Rinaldi (Jurnal Ilmiah Samudra Akuatika, 2023)
The hatchery is a biosecurity system in the form of a water quality control system and aquatic environmental health. Hatchery determines the success or failure of spawning. Temperature, pH and dissolved oxygen are key water quality parameters that control the distribution and distribution of organisms in the waters. Temperature, pH and dissolved oxygen in waters are key water quality parameters that control the distribution and distribution of organisms in the waters. This study aims to describe fluctuations in water quality, namely temperature, pH, and DO in the indoor hatchery based on different times. The design used was a RAL with 3 treatments and 4 repetitions, namely P1: observing water parameters every 1 hour (6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 WIT); P2: observation of water parameters every 2 hours (6, 8, 10, 12, 14, 16, 18, 20, 22, 24 WIT); and P3: observation of water parameters every 4 hours (6, 10, 14.18, 22 WIB). The results showed that in general the temperature, DO and pH values ​​in the indoor hatchery did not fluctuate significantly. However, during the observation at 14 to 16 WIB at P1 there was an increase in temperature and DO, on the contrary there was a decrease in the pH value. When DO increases, the pH appears to decrease. At P2 there was a decrease in temperature values ​​at 6 to 8 WIB, while the DO and pH values ​​were stable. Furthermore, at P3, it can be seen that the temperature, DO and pH values ​​are more stable.